Evidence of a Fraction of LIGO/Virgo/KAGRA Events Coming from Active Galactic Nuclei - Liang-Gui Zhu; Xian Chen (The Astrophysical Journal Letters)
The formation channels of the gravitational-wave (GW) sources detected by LIGO/Virgo/KAGRA (LVK) remain poorly constrained. Active galactic nucleus (AGN) has been proposed as one of the potential hosts, but the fraction of GW events originating from AGNs has not been quantified. Here, we constrain the AGN-origin fraction f _agn by analyzing the spatial correlation between GW source localizations ( O 1– O 4a) and AGNs (Sloan Digital Sky Survey 16th data release). We report preliminary evidence of an excess of lower-luminosity (10 ^44.5  ≲  L _bol ≤ 10 ^45 erg s ^−1 ) as well as lower-Eddington ratio (0.01 ≲  λ _Edd ≤ 0.05) AGNs around the LVK events, the explanation of which requires ${f}_{{\rm{agn}}}=0.3{9}_{-0.32}^{+0.41}$ and $0.2{9}_{-0.25}^{+0.40}$ (90% confidence level) of the LVK events originating from these respective AGN populations. Monte Carlo simulations confirm that this correlation is unlikely to arise from random coincidence, further supported by anomalous variation of the error of f _agn with GW event counts. These results support the theoretical speculation that some LVK events come from lower-luminosity or lower-accretion-rate AGNs, offering critical insights into the environmental dependencies of the formation of GW sources.